Adversity, emotion regulation, and non-suicidal self-injury in eating disorders - Vieira, Ana Isabel (2016)
The comorbidity between non-suicidal self-injury and eating disorder behaviors suggests that psychosocial factors may play a role in both types of behaviors. This study aimed to assess the presence of non-suicidal self-injury in 66 eating disorder patients and to analyze the associations among adversity, emotion regulation, non-suicidal self-injury, and disordered eating behavior. A total of 24 participants (36.4%) reported non-suicidal self-injury. Patients endorsing self-injury had a higher severity of disordered eating behavior. More difficulties in emotion regulation and a greater number of methods of non-suicidal self-injury were associated with a higher severity of eating pathology. Clinicians should consider these relationships in the assessment and treatment of eating disorders.